Border watch : cultures of immigration, detention and control - Hall, Alexandra (Lecturer in political science) (Anthropology, culture, and society., 2012)
Questions over immigration and asylum face almost all Western countries. Should only economically useful immigrants be allowed? What should be done with unwanted or 'illegal' immigrants? In this bold and original intervention, Alexandra Hall shows that immigration detention centres offer a window onto society's broader attitudes towards immigrants. Despite periodic media scandals, remarkably little has been written about the everyday workings of the grassroots immigration system, or about the people charged with enacting immigration policy at local levels. Detention, particularly, is a hidden side of border politics, despite its growing international importance as a tool of control and security. This book fills the gap admirably, analysing the everyday encounters between officers and immigrants in detention to explore broad social trends and theoretical concerns.